2015
DOI: 10.1105/tpc.16.00100
|View full text |Cite
|
Sign up to set email alerts
|

A Land Plant-Specific Transcription Factor Directly Enhances Transcription of a Pathogenic Noncoding RNA Template by DNA-Dependent RNA Polymerase II

Abstract: Some DNA-dependent RNA polymerases (DdRPs) possess RNA-dependent RNA polymerase activity, as was first discovered in the replication of Potato spindle tuber viroid (PSTVd) RNA genome in tomato (Solanum lycopersicum). Recent studies revealed that this activity in bacteria and mammals is important for transcriptional and posttranscriptional regulatory mechanisms. Here, we used PSTVd as a model to uncover auxiliary factors essential for RNA-templated transcription by DdRP. PSTVd replication in the nucleoplasm gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
106
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(112 citation statements)
references
References 57 publications
3
106
0
Order By: Relevance
“…Their RNAs form rod-shaped secondary structures but likely lack ribozyme activities (2,16). Potato spindle tuber viroid (PSTVd) requires a unique splicing variant of transcription factor IIIA (TFIIIA-7ZF) to replicate by Pol II (17) and optimizes expression of TFIIIA-7ZF through a direct interaction with a TFIIIA splicing regulator (ribosomal protein L5, a negative regulator of viroid replication) (18). The molecular basis of viroid pathogenicity is not fully understood, although some mechanisms have been suggested, including the down-regulation of host gene expression via RNA silencing-mediated degradation guided by viroid-derived small RNAs (19)(20)(21).…”
mentioning
confidence: 99%
“…Their RNAs form rod-shaped secondary structures but likely lack ribozyme activities (2,16). Potato spindle tuber viroid (PSTVd) requires a unique splicing variant of transcription factor IIIA (TFIIIA-7ZF) to replicate by Pol II (17) and optimizes expression of TFIIIA-7ZF through a direct interaction with a TFIIIA splicing regulator (ribosomal protein L5, a negative regulator of viroid replication) (18). The molecular basis of viroid pathogenicity is not fully understood, although some mechanisms have been suggested, including the down-regulation of host gene expression via RNA silencing-mediated degradation guided by viroid-derived small RNAs (19)(20)(21).…”
mentioning
confidence: 99%
“…Viroids are circular noncoding RNAs that infect crop plants, often leading to plant disease (Ding, 2009, Flores et al, 2014. As infectious noncoding RNAs, viroids have been a productive model to dissect plant defense mechanisms against invasive RNAs (Itaya et al, 2007, St-Pierre et al, 2009, Zheng et al, 2017, the role of RNA three-dimensional motifs in regulating RNA systemic trafficking (Ding, 2009, and RNA-templated RNA replication by DNA-dependent RNA polymerase II (Pol II) (Rackwitz et al, 1981, Wang et al, 2016. Recent progress has begun to elucidate how viroids co-opt cellular factors to effectively propagate themselves (Flores et al, 2005, Ding, 2009, Nohales et al, 2012a, Nohales et al, 2012b, Minoia et al, 2014, Katsarou et al, 2016, Wang et al, 2016, Dissanayaka Mudiyanselage et al, 2018, Jiang et al, 2018.…”
Section: Discussionmentioning
confidence: 99%
“…PSTVd, and viroids in family Pospiviroidae, employ Pol II for transcription (Rackwitz et al, 1981). A splicing variant of TFIIIA (TFIIIA-7ZF) facilitates Pol II-catalyzed transcription using PSTVd RNA template (Wang et al, 2016). Interestingly, the splicing of TFIIIA transcripts is regulated through a direct interaction between PSTVd and ribosomal protein L5 (RPL5), which results in optimal expression of TFIIIA-7ZF favoring PSTVd transcription (Jiang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This is further supported by the findings where N. benthamiana canonical 9‐zinc finger (ZF) Transcription Factor IIIA (TFIIIA‐9ZF) and its variant TFIIIA‐7ZF interacted with (+) strand of PSTVd whereas only TFIIIA‐7ZF found to interact with (−) strand of PSTVd. In planta experiments revealed that the expression of TFIIIA‐7ZF directly correlates with PSTVd replication (Wang et al, ). More recently, in vitro and in vivo studies revealed that, PSTVd favor the expression of TFIIIA‐7ZF, thereby promoting its replication by directly interacting with a splicing regulator, RPL5 with CCR, which is critical for PSTVd replication (Dissanayaka Mudiyanselage, Qu, Tian, Jiang, & Wang, ; Jiang et al, ).…”
Section: Viroid Pathogenicity and Host Componentsmentioning
confidence: 99%